2015
DOI: 10.1136/heartjnl-2014-306670
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol use and risk of non-fatal acute myocardial infarction

Abstract: The present study supports the hypothesis that allopurinol is associated with a reduced risk of non-fatal AMI, which seems to be dose-dependent and duration-dependent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 28 publications
6
34
1
5
Order By: Relevance
“…This is similar to a lower risk of cardiovascular events (including MI) due to allopurinol in a longer follow-up of a randomised study documenting an impact of longer duration 45. In addition, higher allopurinol dose was associated with lower mortality in patients with heart failure29 and lower risk of MI in the general population 25. Thus, potential cardioprotective effects of allopurinol may be related to allopurinol duration and dose.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This is similar to a lower risk of cardiovascular events (including MI) due to allopurinol in a longer follow-up of a randomised study documenting an impact of longer duration 45. In addition, higher allopurinol dose was associated with lower mortality in patients with heart failure29 and lower risk of MI in the general population 25. Thus, potential cardioprotective effects of allopurinol may be related to allopurinol duration and dose.…”
Section: Discussionsupporting
confidence: 63%
“…The study was limited to patients with heart failure and to US veterans, a significant issue with generalisability of study findings; specifics of study methods are not available. Our observation of potential prevention of AF with allopurinol adds to the emerging literature of its cardiovascular beneficial effect for overall cardiovascular outcomes,24 myocardial infarction,25 heart failure readmission or death,26 and mortality 27–29…”
Section: Discussionmentioning
confidence: 76%
“…Finally, a recently published pharmacoepidemiological study found results close to those reported by de Abajo and colleagues,2 with allopurinol use associated with 20% reduced risk of MI 8…”
Section: Urate-lowering Therapiessupporting
confidence: 72%
“…In this context, the report from de Abajo and colleagues2 is of interest: this population-based case-control study found that allopurinol was associated with significantly reduced risk of non-fatal acute MI (OR=0.52 (95% CI 0.33 to 0.83)), mainly in men, with >180 days’ allopurinol exposure and with >300 mg dose.…”
mentioning
confidence: 98%
“…Epidemiological studies suggested that allopurinol might decrease morbidity and mortality in patients with congestive heart failure and a history of gout,118 119 a benefit not confirmed in a recent randomised trial of patients with heart failure and hyperuricaemia without gout 120. In addition, pharmaco-epidemiological studies report that allopurinol use is associated with an approximately 20% reduction in myocardial infarction risk 121 122. However, the task force acknowledged that additional well-conducted trials are warranted in this field, as recent studies yielded conflicting results 123 124…”
Section: Resultsmentioning
confidence: 99%